Analisis Beban Kerja dan Kebutuhan Pegawai di Pusat Perpustakaan dan Penyebaran Teknologi Pertanian (PUSTAKA) - Muhammad Hasrialdy Qamalpasha Muchransyah; Siti Rahmawati (Jurnal Manajemen dan Organisasi, 2016)
Library and Deployment Center for Agricultural Technology (PUSTAKA) is implementing good governance and reform of the bureaucracy but the distribution of employees not comply with existing workload. The solution of these problem is make an improvement in management of personnel, carrying out more targeted, have a clear and continous pattern. The objectives of the research are to analyze the effective working time used by the employees on staff level of PUSTAKA, and to analyze the ideal number of the employees needed on staff level of PUSTAKA using the regulation of Minister Empowerment State Aparatus and Bureaucracy Reform number 75 year 2004. The method used in calculating workload  using full time equivalent and calculating needs of employee using regulation of Minister Empowerment State Aparatus and Bureaucracy Reform number 75 year 2004.  The results shows that the effective working time of employees is 90.652,5 minutes or 237 effective working days during the year and the number of employees needed of each sub-section/sub-field in general not in accordance with the needs of the ideal employee.